Ethylene mediates salicylic-acid-induced stomatal closure by controlling reactive oxygen species and nitric oxide production in Arabidopsis. (May 2020) - Wang, Hui-Qin; Sun, Li-Ping; Wang, Li-Xiao; Fang, Xiao-Wei; Li, Zhong-Qi; Zhang, Fang-Fang; Hu, Xin; Qi, Cheng; He, Jun-Min
Highlights: NPR1 mediates SA-induced ethylene production by activating the expression of ACS2/6/11. Ethylene synthesis and signaling are required for SA-induced stomatal closure. ATRBOHD/F-generated ROS and NIA1/2-generated NO are required for SA guard cell signaling. Ethylene mediates SA-induced ROS in an RAN1-, ETR1- and CTR1-dependent manner. ROS mediates SA-induced NO through the ETR1, EIN2, EIN3 and ARR2-dependent pathway(s). Abstract: Both salicylic acid (SA) and ethylene induce stomatal closure and positively regulate stomatal immunity, but their interactions in guard cell signaling are unclear. Here, we observed that SA induced the expression of ethylene biosynthetic genes; the production of ethylene, reactive oxygen species (ROS) and nitric oxide (NO); and stomatal closure in Arabidopsis thaliana . However, SA-induced stomatal closure was inhibited by an ethylene biosynthetic inhibitor and mutations in ethylene biosynthetic genes, ethylene-signaling genes [ RESPONSE TO ANTAGONIST 1 ( RAN1 ), ETHYLENE RESPONSE 1 ( ETR1 ), ETHYLENE INSENSITIVE 2 ( EIN2 ), EIN3 and ARABIDOPSIS RESPONSE REGULATOR 2 ( ARR2 )], NADPH oxidase genes [ ATRBOHD and ATRBOHF ], and nitrate reductase genes ( NIA1 and NIA2 ). Furthermore, SA-triggered ROS production in guard cells was impaired in ran1, etr1, AtrbohD and AtrbohF, but not in ein2, ein3 or arr2 . SA-triggered NO production was impaired in all ethylene-signaling mutants tested and in nia1 and nia2 . The stomata of mutants for CONSTITUTIVE TRIPLE RESPONSE1 ( CTR1 ) showed constitutive ROS and NO production and closure. These results indicate that ethylene mediates SA-induced stomatal closure by activating ATRBOHD/F-mediated ROS synthesis in an RAN1-, ETR1- and CTR1-dependent manner. This in turn induces NIA1/2-mediated NO production and subsequent stomatal closure via the ETR1, EIN2, EIN3 and ARR2-dependent pathway(s).